The Impact of Augmented Reality Integrated Mobile Learning on High School Students’ Creative Thinking Skills in Chemistry - Ucu Cahyana; Woro Puspawati; Ariyatun Ariyatun; Setia Budi (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
The aim of this study was to examine the Augmented Reality (AR) Integrated Mobile Learning for enhancing creative thinking skills in high school chemistry students. The research employed an experimental method, utilizing creative thinking tests as the data collection instrument. Both control and experimental groups were involved, comprising a total of 72 upper secondary school students studying chemistry. Data analysis included normality and homogeneity tests. The findings indicated a significant improvement in students’ creative thinking abilities. A conceptual model was developed, demonstrating that AR-integrated mobile learning could enhance creative thinking through several key factors: media characteristics, learning management, pedagogical principles, and technical aspects of the media. The study recommends incorporating technology skills from teachers, students, and available resources, which could potentially yield different outcomes. These findings imply that educational policymakers and curriculum developers should consider integrating AR-based mobile learning platforms into national chemistry curricula to systematically foster students' creative thinking skills in alignment with 21st-century learning demands.